Comparison of the Efficacy of Generation 1 and 2 Tyrosine Kinase Inhibitors in Non-Small Cell Lung Cancer Patients with EGFR Positive Mutations - Suwandi; Laksmi Wulandari; Gatot Soegiarto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The use of TKI generation 1 (Gefitinib, Erlotinib) and Generation 2 (Afatinib) has become thestandard therapy for JPIC pulmonary adenocarcinoma type with positive EGFR gene mutations.Objective: to analyze the comparison of the efficacy of TKI generation 1 and 2 in NSCLC patients withpositive EGFR mutations.Methods: The design of this study used a retrospective in which the participants who received EGFR therapyfor TKI generations 1 and 2 were compared its efficacy. Data collected included health-related quality of life(HRQOL), body weight, performance status (PS), Response Evaluation Criteria in Solid Tumors (RECIST)of thoracic CT, Common Terminology Criteria for Adverse Events (CTCAE), progression free survival(PFS) and overall survival (OS). The statistical analysis used was the independent t test, Mann Whitney test,or Kruskal Wallis test with p <0.05.Results: Most of the participants’ quality of life scores did not change before and after therapy, where theEQ5D value was 67.5% (group 1 = 60.6%; Group 2 = 94.1%; p = 0.806). The participant’s weight decreasedby 49.5% (group 1 = 45.9%; group 2 = 60.0%; p = 0.658) and the participant’s PS was stable (group 1 =29.4%; group 2 = 50.0%; p = 0.014). The RECIST value of the participant was progressive disease 51.0% (p= 0.338). CTCAE differed in stomatitis (p <0.001), paronychia (p <0.001), and diarrhea (p <0.001). Therewas no significant difference between the first and second groups in the PFS (p = 0.197) and OS (p = 0.740)values.Conclusion: EGFR therapy for TKI generations 1 and 2 have almost the same efficacy, in which there is nosignificant difference in the quality of life of the participants.